(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the extent to which cloud computing technology can be used in organizing accounting operations at the branches of Jumhouria Bank (Souq Al-Khamis, Esbi’a, and Souq Al-Ahad). The study adopted the descriptive-analytical approach and used a questionnaire as the primary tool for data collection. Statistical data obtained from 39 questionnaires were analyzed. The findings revealed that there is currently no possibility of using cloud computing technology in organizing accounting operations at the three branches of Jumhouria Bank. Employees at these branches also believe that implementing cloud computing technology in accounting operations is not easy. Furthermore, the results indicated that cloud computing technology cannot yet be fully trusted or relied upon for organizing accounting work. The study recommended that Jumhouria Bank and its three branches move toward adopting cloud computing technology in organizing accounting operations. It also emphasized the need to facilitate the use of cloud computing in accounting processes, enhance confidence in and reliance on this technology, and provide employees with the necessary training before implementation. In addition, the study recommended developing solutions to overcome any obstacles that may face the bank and its branches during the transition to and implementation of cloud computing technology.